Diversity and Inclusion in Global Higher Education 2020
DOI: 10.1007/978-981-15-1628-3_9
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Sexual Diversity in Asian Universities

Abstract: committed suicide after his sexual orientation was made public against his will in August 2015. 2 A year after his death, two students from the same university started a student group to foster a safe space for LGBTQ students on campus; the group was officially recognized by the university in May 2017. 3 These two examples from Indonesia and Japan demonstrate firstly, the serious challenges that continue to face LGBTQ university students across Asia and secondly, the different institutional approaches toward L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
0
1
Order By: Relevance
“…We found that 78.6% of medical schools reported teaching some related content. This percentage is above what was previously reported by other studies; for instance, only 27.5% of Japanese medical schools reported teaching some of these topics [ 15 ], which could be explained by contextual factors such as strong cultural taboos around sexuality and intimacy in Asia [ 23 ].…”
Section: Discussioncontrasting
confidence: 53%
“…We found that 78.6% of medical schools reported teaching some related content. This percentage is above what was previously reported by other studies; for instance, only 27.5% of Japanese medical schools reported teaching some of these topics [ 15 ], which could be explained by contextual factors such as strong cultural taboos around sexuality and intimacy in Asia [ 23 ].…”
Section: Discussioncontrasting
confidence: 53%
“…Systematic reviews on LGBTQ+ individuals in Asia have indicated that these individuals frequently express reservations about disclosing their sexual orientation to both healthcare providers and family members due to the prevalence of conservative family values and homonegative attitudes (Breen et al, 2020; Tan & Saw, 2022). This trend persists even in Taiwan, despite the recent legalization of same‐sex marriage in Taiwan (the first to do so in Asia; Au, 2022; Eng & Yang, 2020), which can shape the romantic relationship experiences of LGBTQ+ emerging adults in Asia. Thus, there is a need to ensure the inclusion of LGBTQ+ Asian emerging adults, with sensitivity to the challenges they face.…”
Section: Discussionmentioning
confidence: 99%